Distributed computing and internet technology : 12th International Conference, ICDCIT 2016, Bhubaneswar, India, January 15-18, 2016 : proceedings /: 12th International Conference, ICDCIT 2016, Bhubaneswar, India, January 15-18, 2016 : proceedings. ([2016]) - Unknown
No abstract available